Effect of lipopolysaccharide addition on the gene transfection of spermine-introduced pullulan-plasmid DNA complexes for human mesenchymal stem cells. Issue 16 (2nd November 2019) - Ueda, Masumi; Jo, Jun-Ichiro; Gao, Jian-Qing; Tabata, Yasuhiko
Abstract: The objective of this study is to investigate the effect of lipopolysaccharide (LPS) addition on the gene transfection of human mesenchymal stem cells (hMSC). hMSC were treated with the LPS at different concentrations and the complex of spermine-introduced pullulan and luciferase plasmid DNA for 3 h. The maximum level of gene expression was observed for hMSC treated with a certain concentration range of LPS. In addition, the cytotoxicity, cellular internalization of complexes, and cell cycle after LPS treatment were investigated. The cytotoxicity increased with an increase in the LPS concentration treated. On the other hand, the cellular internalization of complexes increased with the increased LPS concentration, although the internalization was sharply reduced at the high concentration. The LPS treatment increased the actin polymerization of cells to allow to spread more. The enhanced cells spreading would enhance the cellular internalization of complexes. In addition, the LPS treatment increased the rate of cell cycle. It is possible that the balance of cytotoxicity, cellular internalization, and cell cycle caused by the LPS addition results in the enhanced gene transfection at a certain LPS concentration. It is concluded that LPS treatment positively modified the cellular internalization and the cell cycle, resulting in the enhanced gene transfection.